Functional impact of post-exercise cooling and heating on recovery and training adaptations: application to resistance, endurance, and sprint exercise - Chaillou, T.; Treigyte, V.; Mosely, S.; Brazaitis, M.; Venckunas, T.; Cheng, A. J. (Sports Medicine - Open, 2022)
The application of post-exercise cooling (e.g., cold water immersion) and post-exercise heating has become a popular intervention which is assumed to increase functional recovery and may improve chronic training adaptations. However, the effectiveness of such post-exercise temperature manipulations remains uncertain. The aim of this comprehensive review was to analyze the effects of post-exercise cooling and post-exercise heating on neuromuscular function (maximal strength and power), fatigue resistance, exercise performance, and training adaptations. We focused on three exercise types (resistance, endurance and sprint exercises) and included studies investigating (1) the early recovery phase, (2) the late recovery phase, and (3) repeated application of the treatment. We identified that the primary benefit of cooling was in the early recovery phase (< 1 h post-exercise) in improving fatigue resistance in hot ambient conditions following endurance exercise and possibly enhancing the recovery of maximal strength following resistance exercise. The primary negative impact of cooling was with chronic exposure which impaired strength adaptations and decreased fatigue resistance following resistance training intervention (12 weeks and 4-12 weeks, respectively). In the early recovery phase, cooling could also impair sprint performance following sprint exercise and could possibly reduce neuromuscular function immediately after endurance exercise. Generally, no benefits of acute cooling were observed during the 24-72-h recovery period following resistance and endurance exercises, while it could have some benefits on the recovery of neuromuscular function during the 24-48-h recovery period following sprint exercise. Most studies indicated that chronic cooling does not affect endurance training adaptations following 4-6 week training intervention. We identified limited data employing heating as a recovery intervention, but some indications suggest promise in its application to endurance and sprint exercise.